Context-Dependent Risk Preferences and Decoy Effects - Fabian Herweg; Daniel Müller; Asri Özgümüs; Fabio Römeis (CESifo GmbH, 2025)
We present a theory of context-dependent risk preferences under which within-state payoff comparisons and regret aversion shape decisions. Defining the attraction and compromise effect in reference to a state-space-based description of the choice problem, we show that our theory can account for both these prominent decoy effects. We test our theoretical predictions with an online experiment, including comparative statics results. We find strong evidence for the attraction and the compromise effect. Furthermore, we find some supportive evidence for our comparative static predictions and weakly diminishing sensitivity regarding ex-post regret.
Keywords: C91; D010.D810; D91; M31; 330; asymmetric dominance effect; attraction effect; compromise effect; context-dependent preferences; correlation-sensitive preferences; decoy effect; regret theory